2013 year in review – state advanced energy legislation - Center for the New Energy Economy, author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2013)
This paper outlines CNEE's analysis of the 589 advanced energy bills that have been enacted this year.
Keywords: Energy policy; Renewable energy sources -- Law and legislation -- United States; Advanced Energy Legislation Tracker